Maternal CD8+ T‐cell depletion alleviates intrauterine inflammation‐induced perinatal brain injury. (4th December 2017) - Lei, Jun; Xie, Li; Zhao, Hongxi; Gard, Candice; Clemens, Julia L.; McLane, Michael W.; Feller, Mia C.; Ozen, Maide; Novak, Christopher; Alshehri, Wael; Alhejaily, Nader; Shabi, Yahya; et al.
Abstract : We investigated the mechanisms by which CD8 + T‐cell trafficking in placenta contributes to perinatal brain injury by studying effects of maternal CD8 + T‐cell depletion (DEP) in a mouse model of intrauterine inflammation (IUI). Maternal CD8 + T cells were depleted with anti‐CD8 + antibodies. IUI was induced with lipopolysaccharide (LPS). DEP was confirmed using flow cytometry. Preterm birth rate was evaluated. Offspring neurologic sequelae were assessed by Nissl staining, immune arrays, confirmatory individual TaqMan ® gene assays, and neurobehavioral tests. DEP did not significantly prevent LPS‐induced preterm birth but improved neurobehavioral performance ( P  < .001) and increased cortical neuronal density ( P  < .05) in LPS‐exposed pups compared to controls. These changes were associated with decreased CCL3 and CXCL10 and increased CCL5 in DEP LPS‐exposed mice. We demonstrate that DEP reduces perinatal brain injury following IUI. This supports a role for maternal CD8 + T‐cell trafficking in placenta in mediating perinatal brain injury separate from preterm birth mechanisms. Abstract : Maternal CD8 + T cell depletion prior to exposure to maternal intrauterine inflammation acted to improve perinatal brain injury. Neurobehavioral outcomes and cortical neuronal counts (Nissl staining) were improved in offspring of mice who underwent CD8 + T cell depletion prior to lipopolysaccharide (LPS) injection, compared to LPS alone. These data indicate the importance of maternal CD8 + T cells in shaping the offspring's response to maternal inflammation.